PENGARUH MODEL PEMBELAJARAN JIGSAW BERBANTU MEDIA GAMBAR TERHADAP HASIL BELAJAR IPA SISWA KELAS IV - Khusnul Fajriyah; Primadylla Anggiadhani (Universitas PGRI Semarang, 2015)
The background of this research is based on the lack of students?óÔé¼Ôäó activity and the lowest of the students outcome, it because they were not interested in Science. The objective of this research is to find out the influences of Jigsaw?óÔé¼Ôäós learning model to helps the students?óÔé¼Ôäó outcome in learning Science for the Fourth Grade Students of SD Negeri Bandungrejo 01 Mranggen, such as, the teacher?óÔé¼Ôäós performance, students activity, and the outcome of the study. Based on the result of this research, it shows the average before using Jigsaw was 60 increasing to 81. Thus, this analysis obtained ttest at 11.826 while ttabel with db = 32-1 = 31 and 0.05 significance level of 1.684. Because thitung> ttabel ie 11.826> 1.684, then Ho is rejected and Ha is accepted or it can be said that there is influence of Jigsaw?óÔé¼Ôäós Learning Model for science learning for the fourth grade students of SDN Bandungrejo 01 Mranggen. The observations during Jigsaw learning activities by using pictures give the increase result of students?óÔé¼Ôäó activity. Based on the teacher?óÔé¼Ôäós result while doing the research is 87 and it can be conclude the criteria of teacher?óÔé¼Ôäós performance is good.